Applying Western models of volunteering in Hong Kong: The role of empathy, prosocial motivation and motive–experience fit for volunteering. Issue 2 (20th January 2016) - Aydinli‐Karakulak, Arzu; Bender, Michael; Chong, Alice Ming Lin; Yue, Xiaodong
Abstract : The present research investigates the applicability of prominent Western volunteering frameworks in Hong Kong. Two cross‐sectional surveys involving a total of 268 respondents were conducted. In Study 1, we tested a model of volunteering among 149 Hong Kong Chinese adult individuals ( Mage  = 34.8 years; 51.7% female) that examines antecedents and outcomes of voluntary engagement. Results show that prosocial motivation relates to volunteering, and that volunteering in turn predicts life satisfaction. Unexpectedly, and unlike studies in Western settings, other‐oriented empathy was not related to volunteering. Study 2 tests the propositions of the Volunteer Process Model (VPM) among 119 Hong Kong Chinese volunteers ( Mage  = 36.9 years; 58.0% female). Findings largely support the VPM: our results indicate that the link between motives, voluntary service length and frequency is mediated by satisfaction with volunteering. Moreover, findings suggest that a fit between motives and experience seems relevant for increasing volunteers' satisfaction with their service. Results of both studies suggest that Western volunteering models can be applied to volunteering in East Asian cultures when culture‐specific adaptations are considered.